The interplay between muscle length, range of motion and exercise selection: a review - Pedrosa, Gustavo Ferreira; Pereira, Mariano Rezende; Kassiano, Witalo (Sports Medicine International Open)
Emerging evidence suggests that training at longer muscle lengths may optimize muscle hypertrophy. Of note, there is an interplay between muscle length, range of motion (ROM), and exercise selection which difficult to identify whether muscle length per se is the main factor, limiting the ability to draw practical conclusions. Thus, synthesizing these different lines of investigation may help to clarify this topic. Firstly, we offer a comprehensive understanding of the physiological effects arising from muscle contractions in longer, moderate, and shorter muscle lengths. Subsequently, we conducted an unstructured review of long-term studies comparing muscle hypertrophy following: 1) isometric training at different muscle lengths, 2) training with different ROMs, and 3) exercises that train muscles at different muscle lengths and/or with different resistance profiles. Different lines of investigation suggest that muscle length plays a role, as training at longer muscle lengths elicits more favorable muscle growth. Notably, the greater muscle growth often observed after exercises and ROMs that train muscles at longer lengths occurs when there is a relevant external torque in the lengthened position. From a practical perspective, the selection of exercises and ROMs that impose relevant external torque at longer muscle lengths should be considered to optimize muscle growth.